Scottish art in the Industrial Age, 1800-1914.
1 online resource (334 pages)
Keywords: This volume focuses on artists and writers associated with the Arts and Crafts movement, Scottish Symbolism and the Celtic Revival. The latter was spearheaded by the biologist and social reformer Patrick Geddes, who encouraged artistic revival in Edinburgh. In 1884 he founded the Edinburgh Social Union which commissioned mural schemes for public buildings from artists such as Phoebe Anna Traquair. Geddes also invited contributions from contemporary artists through his avant-garde journal The Evergreen, whose art editor was John Duncan. During the same period Glasgow flourished as an artistic centre under the leadership of Fra Newbery at Glasgow School of Art. This period saw the rise in importance of the decorative arts and the emergence of a number of women designers, among them Jessie Keppie, Annie French and Ann Macbeth. The leading artists at the turn of the century were Charles Rennie Mackintosh, Herbert McNair and the Macdonald sisters, who enjoyed an international reputation, exhibiting at the Vienna Secession in 1900. Accompanied by extensive editorial commentary, this collection will be of great interest to students of Art History and Scottish History.